PERSEPSI GURU EKONOMI TERHADAP PENERAPAN KURIKULUM MERDEKA DENGAN PENDEKATAN DEEP LEARNING DI SMA NEGERI 1 TANJUNG JABUNG TIMUR - Silvi Oktaviani; Muazza Muazza; Novia Sri Dwijayanti (STKIP Pesisir Selatan, 2026)
This This study aims to describe teachers' understanding of the Independent Curriculum and the Deep Learning approach, analyze its application in economics learning, and identify challenges and strategies used by teachers at SMA Negeri 1 Tanjung Jabung Timur. This study used a qualitative approach with a descriptive phenomenological approach. The research subjects consisted of economics teachers as the primary informants, and the principal and vice principal for curriculum as supporting informants selected through purposive sampling. Data collection was conducted through interviews, observation, and documentation, while data analysis included data reduction, data presentation, and drawing conclusions. The results showed that teachers had a fairly good understanding of the Independent Curriculum and the Deep Learning approach. Learning implementation was carried out through planning, implementation, and evaluation stages that led to active, contextual learning oriented toward students' in-depth understanding. However, implementation still faced obstacles such as limited facilities, teacher readiness, and differences in student abilities. To overcome these obstacles, teachers implemented adaptive strategies such as the use of interactive methods, material adjustments, and collaboration and reflection on learning.